Exploring Nursing Students’ Awareness and Willingness to Participate in Multi-Site Practice: A Cross-Sectional Study - Li F; Huang Q; Xiong L; Lei C; Mou S; Zhou Y; Liang R; Yu H; Zhang H; Ren X; Shi Q (Risk Management and Healthcare Policy)
Fan Li,1,2,* Qi Huang,3,* Lingling Xiong,1 Cheng Lei,4 Shaoyu Mou,5 Yujing Zhou,6 Ruichen Liang,7 Huiting Yu,8 Haihua Zhang,1 Xiaobo Ren,9 Qiuling Shi2 1Department of Otolaryngology-Head and Neck Surgery, Chongqing General Hospital, Chongqing University, Chongqing, People’s Republic of China; 2College of Public Health, Chongqing Medical University, Chongqing, People’s Republic of China; 3Department of Gastroenterology, The Second Affiliated Hospital of Chongqing Medical, Chongqing, People’s Republic of China; 4Sichuan Cancer Hospital & Institute, Sichuan Cancer Center, Affiliate Cancer Hospital of University of Electronic Science and Technology of China, Sichuan, People’s Republic of China; 5School of Nursing, Chongqing Medical University, Chongqing, People’s Republic of China; 6School of Nursing, Chongqing Medical & Pharmaceutical College, Chongqing, People’s Republic of China; 7Operating Room of Affiliated Hospital of Southwest Medical University, Sichuan, People’s Republic of China; 8Guang’an Vocational & Technical College Medical School, Sichuan, People’s Republic of China; 9Beijing Tongren Hospital, Capital Medical University, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qiuling Shi, Email qshi@cqmu.edu.cnBackground: With the growing awareness of health and the expanding aging population, the demand for health services continues to rise. According to statistics from China, the number of professionals engaged in medical and health care services is insufficient to meet the public’s needs, particularly in terms of nursing human resources in medical institutions. Multi-site practice may offer a potential solution to this issue.Aim: To investigate the willingness and motivation of nursing students for multi-site practice of reference and nurse, and to lay a foundation for subsequent research.Research Questions: 1. How much do nursing students know about multi-site practice? What are the main sources of their knowledge of multi-site practice? 2. What are the main intentions and motivations of nursing students to participate in multi-site practice? For example, is it for financial gain, self-worth, or other reasons? 3. What are the potential barriers for nursing students to participate in multi-site practice in the future? For example, will inadequate laws and regulations, occupational safety issues or excessive work load affect their willingness?Methods: This cross-sectional study was conducted across eight provinces in China, involving 1014 nursing students who participated in an online survey between October and November 2021.Results: Among the 1014 nursing students surveyed, 61.74% were introduced to multi-site practice through their educational institutions, 75.25% expressed support for multi-site practice, and 53.75% indicated a willingness to engage in multi-site practice. However, a smaller percentage of students reported having a comprehensive understanding of multi-site practice. Notably, 61.74% of students cited their schools as the primary source of multi-site practice-related knowledge.Conclusion: Nursing students demonstrate positive attitudes toward multi-site practice and a willingness to participate. However, awareness of multi-site practice could be enhanced, and a standardized multi-site practice training system and model should be developed.Keywords: nursing students, multi-site practice, awareness, willingness